REFLEKSI NASIONALISME TOKOH DALAM FILM WATHANI AL-GHALI: TELAAH RESEPSI SASTRA - Erwhintiana, Ifi; Fitriani, Laily (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2021)
This research aims to reveal audiences reflection about propaganda of Palestine Liberation that presented through nationalism value in film wathani al-ghali based on Stuart Hall Perspective. This research is decriptive qualitative. The subject of this research are 40 students of Arabic Languange and Literature in UIN Maulana Malik Ibrahim by purposive sampling based on curent criteria. The results of this research showed that actualization of nationalism value in film wathani al-ghali are about 18 in various form as propaganda of Palestine Liberation. Those actualization are blatant uprising, being killed for Palestine’s defenses, fooling the Israeli army and attacking them. Audience receptions for the representation nationalism value in the film interpreted into a reflection of propaganda of Palestine Liberation. Percentage of audiences are 78% are in dominant hegemony position, 22% are in negoitation position, and no ocucupies for the opposition. Some underlying factors are background knowledge that related to Palestinian conflict, simple flow, and also getting much moral values from the film.